Strategic unemployment - Julia Angerhausen; Christian Bayer; Burkhard Hehenkamp (Universität Dortmund, Wirtschafts- und Sozialwissenschaftliche Fakultät, 2006)
We propose a dynamic model that explains why individuals may be reluctant to pick up work although the wage is above their reservation wage. Accepting low paid work will put them in an adverse position in future wage bargaining, as employers could infer the individual's low reservation wage from his working history. Employers will exploit their knowledge offering low wages to this individual unemployment to signal a high reservation wage.
Keywords: D82; J30; J64; 330; strategic unemployment; asymmetric information; wage bargaining; minimum wage